2023
DOI: 10.1038/s41598-023-27954-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of plant-derived indole and β-carboline alkaloids against human and avian influenza viruses

Abstract: The persistent evolution of drug-resistant influenza strains represents a global concern. The innovation of new treatment approaches through drug screening strategies and investigating the antiviral potential of bioactive natural-based chemicals may address the issue. Herein, we screened the anti-influenza efficacy of some biologically active indole and β-carboline (βC) indole alkaloids against two different influenza A viruses (IAV) with varied host range ranges; seasonal influenza A/Egypt/NRC098/2019(H1N1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Small molecule compound screening has been widely used to identify inhibitors and medicines to be used in potential prevention and treatment strategies for various viral infections, such as severe acute respiratory syndrome coronavirus 2 [14,15], influenza A virus [16], dengue virus [17], and hepatitis C virus [18] infections.…”
Section: Sc Significantly Inhibits Prrsv Replicationmentioning
confidence: 99%
“…Small molecule compound screening has been widely used to identify inhibitors and medicines to be used in potential prevention and treatment strategies for various viral infections, such as severe acute respiratory syndrome coronavirus 2 [14,15], influenza A virus [16], dengue virus [17], and hepatitis C virus [18] infections.…”
Section: Sc Significantly Inhibits Prrsv Replicationmentioning
confidence: 99%
“…Normal bioactive compounds give assurance and diminish the hazard of different constant infections such as cancer, diabetes, and obesity 6,7 . The novel coronavirus serious, intense respiratory disorder coronavirus 2 (SARS-CoV-2), a recently developing viral respiratory infection, is known to cause COVID-19, which is appallingly spreading around the globe and there's no stoppage.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also demonstrated the efficacy of βCs in vivo [9,16]. Their spectrum of antiviral activity includes DNA and RNA viruses, such as HSV [15][16][17], HIV [18], poliovirus (PV) [19], tobacco mosaic virus (TMV) [20], dengue virus 2 (DENV-2) [21] and avian and human influenza A viruses [22]. Particularly, HSV-1 was the first virus reported to be affected by certain βC alkaloids (Eudistomins) obtained from the colonial tunicate Eudistoma olivaceum [23].…”
Section: Introductionmentioning
confidence: 99%